2020
DOI: 10.1016/j.apenergy.2020.114523
|View full text |Cite
|
Sign up to set email alerts
|

How regional differences in cost of capital influence the optimal design of power systems

Abstract: In order to reduce greenhouse gas emissions of the power sector, high shares of renewable power sources need to be integrated into existing systems. This will require vast amounts of investments. Cost of the capital needed for these investments are unevenly distributed among European regions. They show a clear North-South and West-East divide, which has not exhibited significant signs of narrowing in recent years. Power system studies investigating a continent-wide European power system, however, usually assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…A large share of required investments depends on the financing conditions, which exhibit a large regional disparity for renewable energy projects [Schyska and Kies, 2020]. Recent studies confirmed a major impact of financing conditions such as investors' risk premia on the cost of electricity, particularly for renewable energy investments, [e.g., Schmidt, 2014, Egli et al, 2018, Ste↵en, 2018 and analyzed relevant drivers of risk [e.g., , Polzin et al, 2019.…”
mentioning
confidence: 99%
“…A large share of required investments depends on the financing conditions, which exhibit a large regional disparity for renewable energy projects [Schyska and Kies, 2020]. Recent studies confirmed a major impact of financing conditions such as investors' risk premia on the cost of electricity, particularly for renewable energy investments, [e.g., Schmidt, 2014, Egli et al, 2018, Ste↵en, 2018 and analyzed relevant drivers of risk [e.g., , Polzin et al, 2019.…”
mentioning
confidence: 99%
“…Bloomfield et al [82] saw significant uncertainty in power system design due to climate change and pledged for better understanding of this climate uncertainty. Besides uncertainty arising from meteorological data, other uncertainties affect power systems, such as uncertainty in cost assumptions as well as technological developments [83,84]. The relevance of these effects should be compared to the relevance of uncertainty arising from meteorological data.…”
Section: Discussionmentioning
confidence: 99%
“…• As mentioned in the limitations, capital cost for the different carrier types are treated as equal in different countries. Schyska et al [42] have recently shown that a variation of capital cost for investments in renewables across the European countries (which vary strongly because of large economic and political differences) have a profound impact on the distribution of renewables. It also is a reasonable assumption that inhomogeneous carbon prices and inhomogeneous capital cost do partially oppose each other.…”
Section: Discussionmentioning
confidence: 99%